PENGELOLAAN OBJEK WISATA LEMO DAN BUNTU BURAKE DI KABUPATEN TANA TORAJA PROVINSI SULAWESI SELATAN - Christine Elen Matantu (Fakultas Politik Pemerintahan IPDN, 2019)
Management of Tourism Objects for Lemo and Buntu Burake in Tana Toraja Regency, South Sulawesi Province. Some regions of Indonesia have very interesting tourism resources, with natural and cultural diversity, which if managed properly can be a source of regional income. The purpose of this study is to find out and describe tourism objects managed by the community, as well as how the role of the Regional Government in the community of Tana Toraja Regency in managing tourist objects. The research method is carried out using a qualitative approach, with data collection techniques through literature studies and interviews. The results of this study can be used to increase knowledge of tourist objects located in Tana Toraja Regency and are expected to contribute ideas about the management of community-based attractions. Keywords: Lemo, Buntu Burake, Tana Toraja, tour.